BINA’ AL-HAWIYYAH AD-DINIYYAH ‘ABRA AL-‘ARABIYYAH FI MA‘HAD AL-JAMI‘AH BIJAMI‘AT SYARIF HIDAYATULLAH AL-ISLAMIYYAH AL-HUKUMIYYAH: DIRASAH TAHLILIYYAH FI AL-LISANIYYAT AL-HAWIYYATIYYAH - Inayatur Rosyidah; Gufron Gufron; Mohamad Rofik Fitrotulloh (Afshaha: Jurnal Bahasa dan Sastra Arab, 2026)
This study examines the increasing institutional use of Arabic in Indonesian Islamic higher education and its role beyond administrative regulation. Although Arabic is commonly regarded as a marker of religious authority, its function in shaping students’ identities within institutional contexts has received limited scholarly attention. This study aims to analyze how Arabic language practices at Ma’had Al-Jami‘ah, Universitas Islam Negeri Syarif Hidayatullah Jakarta, contribute to the construction of students’ religious–academic identities. Using a descriptive qualitative approach with interpretative analysis within the framework of identity linguistics, this study investigates institutional discourse, everyday linguistic interactions, and symbolic terminology employed in the ma’had environment. Data were collected through non-participatory observation, documentation, and field notes, and analyzed by identifying identity-related linguistic patterns in official announcements, instructional discourse, and daily communication. The findings indicate that institutionalized Arabic terms such as murabbi, ta‘lim, and halaqah function not only as administrative labels but also as linguistic markers that shape normative roles and value orientations within the ma’had structure. At the same time, differences between institutional discourse and students’ interpretations suggest that identity formation occurs through continuous negotiation rather than one-directional institutional control. Thus, Arabic operates both as a medium for transmitting institutional values and as a space in which religious–academic identity is dynamically constructed.